Organize Bad Manual Financial Database of Educational Organization by Bank to Decrease Financial Criminalize - Ruri Koesliandana; Eka Imama Novita Sari; Arnes Yuli Vandika (Bandar Lampung University (UBL), 2014)
On financial document,the database of money flow is important. every people need money. that’s why money is main factor for corruptor to do the corruption. most of educational organization used the manual accountancy. but sometimes, the manual accountancy is not accurate. this condition give a chance for corruptor to do their action. means that the real and accurate accountancy are the golden key to manage the financial of a organization and to decrease the corruption case. the easy way to get the accurate accountancy is using bank help. by had a deal and using the modern tools fro, bank, the owner of organization doesn’t worry about their financial.